Pendidikan, Ekspektasi Usaha, Skala Usaha dan Pengalaman Usaha Terhadap Penggunaan Informasi Akuntansi di UKM Kota Jayapura - Fitri; Fajar Rina Sejati (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
This research aims to examine the influence of education, business expectations, business scale and business experience on the use of accounting information. This research used data from 96 respondents from SMEs in Jayapura City. The research method used in this research is the purposive sampling method, and uses SPSS 21 as analysis software. The data analysis technique uses multiple regression analysis. The research results show that business expectations and business scale do not influence the use of SME accounting information in Jayapura City. Meanwhile, education and business experience positively influence the use of accounting information in SMEs in Jayapura City.